Brand Image as a Determinant of Patient Decision-Making in Inpatient Healthcare Utilization - Martianawati; Tuffaillah Muawina Nur; Ahmad Lathifi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Healthcare has evolved from provider-centered to consumer-oriented models, making brand image crucial in patient decision-making. However, systematic examination of this relationship in developing country healthcare contexts remains limited. This study investigated how brand image dimensions (corporate identity, physical environment, contact personnel, service offerings, and corporate individuality) influence patient decisions for inpatient services at Nahdlatul Ulama Hospital, Tuban, Indonesia. A quantitative cross-sectional study from January to March 2023 using structured questionnaires from 268 inpatients selected through purposive sampling. Brand image dimensions and patient decision-making were measured using 5-point Likert scales. Analysis included descriptive statistics, Spearman’s correlation, and multiple linear regression. All five dimensions collectively influenced patient decision-making (F=42.990, p<0.001), explaining 45.1% of variance. Bivariate analysis showed significant correlations for all dimensions, with physical environment (rho=0.456, p<0.001) and corporate identity (rho=0.399, p<0.001) strongest. However, multivariate analysis revealed only three dimensions independently influenced decisions: service offerings (β=0.318, p<0.001), contact personnel (β=0.184, p=0.024), and corporate individuality (β=0.115, p=0.030). Brand image significantly influences inpatient healthcare decisions, with service offerings, contact personnel, and corporate individuality most influential. Healthcare facilities should develop comprehensive brand strategies emphasizing service quality, patient-staff interactions, and aligned corporate values, highlighting human elements over physical infrastructure.